Análise de fatores ergonômicos na colheita florestal no sul do estado do Espírito Santo - Jesus, André Tavares de (2018)
The growing demand for raw materials from forests has meant that forestry companies have significantly improved their harvesting systems, aiming to increase productivity and improve the well-being of their operators. In this sense, the present work aimed at the ergonomic analysis of semimechanized harvesting activities in the southern state of Espírito Santo. This research was developed in three properties with eucalyptus plantations in sloping areas. The profile and working conditions were analyzed through the application of a questionnaire through individual interviews. The work environment was evaluated by analyzing noise levels, illuminance, vibration and thermal comfort. The postures adopted were analyzed using the OWAS method. And the risks of joint damage were analyzed with the application of 3DSSPP software from the University of Michigan. The results of the workers' profile showed that 100% of the evaluated workers are of the masculine gender, of low education, with good levels of training, with availability of personal protection equipment, more in some cases without custom of continuous use. The form of remuneration between the properties are distinguished between monthly wages and productivity gains. The noise data show that in all analyzes noise is above the limit established by law, thus there is a need to reduce the exposure or protection of these operators. The illuminance levels were above acceptable minima. However, there is a need for protection in the eyes of operators, especially during the summer. The illuminance levels were above acceptable minima. However, there is a need for protection in the eyes of operators, especially during the summer. The vibration levels are above the recommended limits for performing the activities. The thermal comfort analysis showed that all properties require changes in their working regime in summer and spring, especially in the hottest periods of the day, since the calculated IBUTG has exceeded the acceptable minimum of 26, requiring breaks every hour worked . The postures analyzed by the OWAS methods showed that there is a need for changes in the operations of the chainsaw operator especially during the opening of cutting and felling of the trees. For dockers / forklifts, the need for posture suitability may occur gradually over time. Through the analysis performed with the software 3DSSPP, it is possible to verify that for both operators, as well as for dockers / forklifts all postures compromised some articulation of the worker. It is therefore concluded that there should be adjustments in the working environment and in the positions adopted by the operators in order to improve their health, safety and well-being conditions.